2001
DOI: 10.1542/peds.108.1.e13
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Sexual Behavior, Drug Use, Human Immunodeficiency Virus, and Sexually Transmitted Diseases in Northern Thai Youth Using Audio-Computer–Assisted Self-Interviewing and Noninvasive Specimen Collection

Abstract: ABSTRACT. Background. Drug use, unwanted pregnancy, human immunodeficiency virus (HIV) infection, and sexually transmitted diseases are serious health problems among Thai youth. The gravity of these problems demands high-quality data to direct public health policy and prevention programs. Previous studies of stigmatized behaviors have been hampered by participation bias and underreporting. To evaluate sexual behavior, disease, and drug use, we used audio-computer-assisted self-interviewing (ACASI) and noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 21 publications
5
47
1
3
Order By: Relevance
“…In comparison, Thai adolescents in the general population in northern Thailand and Bangkok reported far higher rates of substance use, with alcohol use exceeding 80% and drug use, including methamphetamines and heroin, reported by up to 38% of adolescents. [12][13] Among youths in Bangkok with behaviorally acquired HIV, 70% had used alcohol within the past year. In regard to sexual risk behaviors, more participants (35.2%) reported having engaged in some form of presexual activity, while fewer reported sexual contact and intercourse (3.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, Thai adolescents in the general population in northern Thailand and Bangkok reported far higher rates of substance use, with alcohol use exceeding 80% and drug use, including methamphetamines and heroin, reported by up to 38% of adolescents. [12][13] Among youths in Bangkok with behaviorally acquired HIV, 70% had used alcohol within the past year. In regard to sexual risk behaviors, more participants (35.2%) reported having engaged in some form of presexual activity, while fewer reported sexual contact and intercourse (3.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, teens in the general Thai population reported much higher rates of sexual intercourse, ranging from 7.9% to 50%. 12,13,24,25 In the United States, at least 30% of vertically HIV-infected teens were sexually active, [9][10] and in the Bangkok study among behaviorally HIV-infected youth, all reported sexual activity. 15 However, as presexual behavior typically precedes sexual contact and intercourse, it is possible that rates of sexual contact and intercourse will continue to rise in this cohort, raising concerns for possible future increases in unsafe sexual practices, STI, and unplanned pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kc were much higher in the HIV+ adolescents across all reports: 0.66 vs 0.42 (2-day), 0.92 vs 0.36 (5-day), and 0.92 vs 0.30 (7-day). Van Griensven et al (2001) noted that of all Thai youths with positive drug screens, 85% of adolescent males and 84% of adolescent females selfreported drug use via ACASI.…”
Section: Reliability and Validitymentioning
confidence: 99%
“…Epidemiological studies show high levels of sexual experience among young Thais (Allen et al, 2003;Jenkins et al, 2002;van Griensven et al, 2001). Although visits to commercial sex workers (CSWs) have become more rare (VanLandingham et al, 2002) due largely to a history of focused HIV prevention efforts (Nelson et al, 1996;Rojanapithayakorn & Hanenberg, 1996), unprotected sex within non-commercial sexual relationships remains common (Mills et al, 1997;Jenkins et al, 2002;Lertpiriyasuwat, Plipat, & Jenkins, 2003).…”
Section: Introductionmentioning
confidence: 99%